2022
DOI: 10.31219/osf.io/k3ayb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkeypox is the manifestation of spectral diseases and not of monkeypox virus transmission

Abstract: The sad monkeypox deaths in countries which now include the United States, Spain, Brazil, India, Ecuador and Peru confirm the predictions of the theory of “The origin of the mysterious multi-country monkeypox outbreak in non-endemic countries” of June 2, 2022 which was obtained with the superior Einsteinian method that illustrates the reality in which phenomena occur and deduces only the consequences of the results obtained to ascertain their perfect correspondence with the data of experience and their mutual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The shift in the demographics has been observed 1 because the causes of those that co-manifest to bring about severe outcomes that are now beginning to cause death among the diseases in the spectrum of monkeypox are becoming more widespread among those in whom such conditions are absent. This clearly demonstrates that the origin of monkeypox cases in non-endemic countries which have no epidemiological links to the cases in endemic countries, which is the mystery that the results from which spectral theory of infectious disease pathogenesis emerged have unraveled, 8,17 does not lie in the transmission of the monkeypox virus between men who have had sex with men. These results revealed that the origin of these outbreaks lies in the disappearance of those immunological conditions that permit the monkeypox virus and other causes of the diseases in its spectrum to be harbored uneventfully (asymptomatically) and transmitted undetected in different regions of the world so that a monkeypox outbreak can occur in a non-endemic region without epidemiological links to Africa.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The shift in the demographics has been observed 1 because the causes of those that co-manifest to bring about severe outcomes that are now beginning to cause death among the diseases in the spectrum of monkeypox are becoming more widespread among those in whom such conditions are absent. This clearly demonstrates that the origin of monkeypox cases in non-endemic countries which have no epidemiological links to the cases in endemic countries, which is the mystery that the results from which spectral theory of infectious disease pathogenesis emerged have unraveled, 8,17 does not lie in the transmission of the monkeypox virus between men who have had sex with men. These results revealed that the origin of these outbreaks lies in the disappearance of those immunological conditions that permit the monkeypox virus and other causes of the diseases in its spectrum to be harbored uneventfully (asymptomatically) and transmitted undetected in different regions of the world so that a monkeypox outbreak can occur in a non-endemic region without epidemiological links to Africa.…”
mentioning
confidence: 94%
“…And we are led to such understanding by the results that emerged in the process of constructing, with the Einsteinian method in which knowledge is not obtained through logical deductions but rather by the visualization of reality, those immunological concepts which have eluded us since the time of Pasteur and the laws that connect them which are now referred to as the spectral theory of infectious disease pathogenesis. 7,8,9,10,11,12,13,14,15,16,17,18,19 These results reveal that the response that occurs in the phenomenon of inflammation is not the response through which immunological mechanisms protect the infected and the vaccinated as Mechnikov deduced and therefore that immunity does not have its origin in the destruction of pathogens by cells and substances which have been logically deduced, in the manner of Mechnikov, to be an "immune system." 20 In the reality thus visualized, such inflammatory responses are brought about by pathological mechanisms and when certain diseases in the *immunological spectrum of the infectious disease co-manifest to bring about outcomes (such as those in which encephalitis is observed) because the same pathological mechanisms are influenced by their causes in such events, the outcomes of the events in which they are brought about will be those of the severe kind that are capable of causing death.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…8,9 And in the manner of Mechikov, inflammatory responses have since been seen as immune responses which should protect the infected organism from the severe outcomes of the event in which the infectious disease is brought about. 9.10 But what I found upon illustrating the biological reality from which the spectral theory of infectious disease pathogenesis has emerged, 10,11,12,13,14,15,16,17,18,19,20,21,22 is that this response that occurs in the phenomenon of inflammation is not the response through which immunological mechanisms protect the infected and the vaccinated but rather a response of pathological mechanisms which may not bring about any clinical outcome when they are not influenced by the cause of any disease but which will bring about severe outcomes that are capable of causing death through the co-manifestation of certain diseases in the immunological spectrum of the infectious disease. In this reality, this response which occurs in pathological phenomena only necessitates the appearance of the conditions that permit immunological mechanisms to obstruct the pathway through which pathological mechanisms respond not only to the influences of the pathogen that causes the infectious disease but also in response to the causes of other diseases in the immunological spectrum of the infectious disease.…”
mentioning
confidence: 99%
“…But in reality, pneumonic plague, which is one of the three major forms of plague, is not a single disease that spreads but rather is an outcome of different diseases that appear concomitantly because of the disappearance of the conditions that permit the different diseases in the immunological spectrum of the disease that Yersnia pestis causes to be rendered asymptomatic without the elimination of their causes." 4 This spectral theory of infectious disease pathogenesis, 6,7,8,9,10 according to which the severe outcomes that cause death in the infected are not a direct consequence of transmission of the pathogen but rather of the disappearance of the conditions that permit asymptomatic hosting of 5 the pathogen and other diseases in its immunological spectrum which results in the comanifestation of such diseases and severe outcomes which the spread of the pathogen cannot account for has now, sadly, been confirmed by monkeypox deaths from severe clinical outcomes of different kinds in non-endemic countries which now include Brazil, Spain, India, 11,12 Ecuador, 13 Peru, 12 the United States, 14,15 Mexico and Cuba. 16 But in the absence of the knowledge of the reality which has yielded the spectral theory of infectious disease pathogenesis, how the monkeyvirus brings about different severe clinical outcomes, which include those with encephalitis, could not be explained.…”
mentioning
confidence: 99%